PENCEGAHAN MELALUI PENYULUHAN MENGENAI STUNTING DEMI MEWUJUDKAN ZERO NEW STUNTING DESA SINDANGMULYA - Purnama, Teuku Tegar; Safutri Asri, Selsi; Hafizh, Muhammad; Ramadani, Nia; Pujihastuti, Isti; Irham (Universitas Islam 45 Bekasi, 2024)
Sindangmulya Village is one of the areas that has a stunting malnutrition problem of 150 children under five. Stunting is a serious problem for the Indonesian people. This is indicated by the large number of cases of stunting in children aged 0 to 3 years. The aim of this service activity article is to improve and reduce the number of stunting in achieving no new growth in Sindangmulia Village. The method used in this outreach activity is to provide short-term seminars by recruiting resource persons. This service activity was carried out in Sindangmulya village, aimed at village residents who still lacked stunting education. The result of this service activity is increased knowledge and awareness, as well as community participation in the prevention and early detection of depression in young children, so that it can motivate the community to contribute to children's growth and development their children. From outreach activities about stunting in Sindangmulya Village, it shows that this program has succeeded in increasing the knowledge and skills of mothers in preventing stunting, with a significant positive impact on community health